Imidazole alkaloids inhibit the pro-inflammatory mechanisms of human neutrophil and exhibit anti-inflammatory properties in vivo. (16th January 2019) - Rocha, Talita Magalhães; Machado, Nuno J; de Sousa, João Antonio Costa; Araujo, Emmanuel Vinicius Oliveira; Guimaraes, Maria Adelaide; Lima, David Fernandes; Leite, José Roberto de Souza de Almeida; Leal, Luzia Kalyne Almeida Moreira
Abstract: Objectives: Epiisopiloturine (EPI) and epiisopilosine (EPIIS) are side products in the pharmaceutical industry. The present study aimed to investigate the anti-inflammatory potential of the alkaloids EPI and EPIIS in human neutrophils and mechanical hyperalgesia in mice. Methods: Neutrophils (5 × 10 6 cells/ml) incubated with EPI and EPIIS and stimulated by the addition of N-formyl-methionyl-leucyl-phenylalanine or phorbol 12-myristate-13-acetate. The release of myeloperoxidase (MPO), reactive oxygen species (ROS) production, calcium influx, gene expression of NF-κB and pro-inflammatory cytokines production were evaluated. It was also investigated the effect these alkaloids on carrageenan-induced mechanical hyperalgesia model in mice. Key findings: We demonstrated that both EPI and EPIIS inhibited the degranulation of activated neutrophils. This effect was accompanied by the reduction in ROS, the prevention of the increase in intracellular Ca 2+ and decrease in the density of cytosolic NF-κB, and inhibition of TNF-α and IL-6 production. Evaluating hypernociception in mice, EPI and EPIIS inhibited carrageenan-induced inflammatory hypernociception and reduced MPO levels. Conclusions: The results obtained suggest EPI and EPIIS not only inhibit neutrophils functions in vitro, but also exhibits anti-inflammatory properties in vivo, acting through the modulation of the activation and/or accumulation of neutrophils in the inflammatory focus. Thus, EPI and EPIIS possess promising anti-inflammatory therapeutic potential.